Association Of Cigarette Smoking With Anxiety, Depression, And Suicidal Ideation Among Brazilian Adolescents - Slomp FM (Dove Medical Press, 2019)
Fátima Martinez Slomp,1,2 Tiago S Bara,1,3 Gledson Luiz Picharski,1,3 Mara L Cordeiro1–4 1Faculdades Pequeno Príncipe, Curitiba, Brazil; 2Guarapuava Centre-West University, Guarapuava, Brazil; 3Research Institute Pelé Pequeno Príncipe, Curitiba, Brazil; 4Department of Psychiatry and Biobehavioral Sciences, David Geffen School of Medicine, Semel Institute for Neuroscience and Human Behavior, University of California Los Angeles, Los Angeles, CA, USACorrespondence: Mara L Cordeiro Av. Silva Jardim 1632, Curitiba, PR, Brazil80250-120 Tel +55 41 3310-1035Email mcordeiro@mednet.ucla.eduBackground: Several studies worldwide have pointed to depression and anxiety symptoms as being related to adolescent smoking. The aim of this study was to investigate, the potential link of cigarette smoking with depression, anxiety, and suicidal ideation and the influence of gender on these relationships in Brazilian adolescents.Methods: Associations of smoking with Children Depressive Inventory version 2 (CDI2) scores, Hamilton Anxiety Scale (HAM-A) scores, and poor school performance (i.e., grade retention) were examined in 988 Brazilian students (age range, 11–17 years) enrolled in 82 public and private schools. Logistic regression modeling was employed and the resultant odds ratios (ORs) are reported with 95% CIs.Results: Of 988 participants, 240 (24.3%) were smokers. Mean (±standard error) HAM-A scores were higher for smokers (21.1 ± 9.7) than nonsmokers (15.4 ± 8.6; p < 0.0001). Relative to nonsmokers, smokers had higher total CDI2 scores (p = 0.033), and higher scores for the CDI2 domains of Emotional Problems (p = 0.023), Negative Self-esteem (p < 0.001), and Functional Problems (p = 0.046). Suicidal ideation was common among smokers with depressive symptoms (54.2%). Smoking was associated with being held back three grades (p < 0.001). Female smokers were more likely to report suicidal ideation than male smokers (p = 0.020). Logistic regression modeling revealed significant associations of suicidal ideation with being female (OR, 1.81; 95% CI, 1.38–2.37), being a female smoker (OR, 2.05; 95% CI, 1.51–2.80), and having a HAM-A score > 16 (OR, 2.18; 95% CI, 1.66–2.86).Conclusion: Smoking was found to be associated with anxiety symptoms, depressive symptoms, and poor school performance in Brazilian adolescents; and female smokers reported more suicidal ideation than male smokers.Keywords: smoking, adolescence, depression, anxiety, suicide, school performance